Analisis Kesalahan Siswa dalam Menyelesaikan Soal Program Linier Bentuk Cerita Berdasarkan Metode Analisis Kesalahan Newman Pada Siswa Kelas XI IPS MAN Salatiga Tahun 2016/2017 - Mahmudah, Itsna Dzuriyati, Dra. Sri Sutarni, M.Pd (2017)
Comprehension ability of students in learning greatly affected a person when would be effect finished a problem. Mistakes were made by students also able to identify the extent of the students' understanding of the material. From the were mistakes made by the students would the effected in learning results obtained by the students. To prohibit this problem repeatedly and to improve learning outcomes it is necessary to the conduct of error analysis.This research aimed to determine the types of error and the cause of the students made mistakes in solving linear programming story form. This research was descriptive qualitative research. These research subjects ware 37 students from class XI IPS 1 MAN Salatiga. Technique of data in this research is to using the test method, interviews, and documentation. Data validation was done by triangulation technique by comparing the test data, interviews, and documentation. Data analysis technique was done by means of data reduction, data presentation, and verification of data and making onclusions. Based on the analysis we concluded that (1) 42.55% of students experienced a transformation error with a medium qualification level error, (2) 32.98% of students experienced inprocessskill errorwith the level of qualification low error, and (3) 24.47% of students experienced in encoding error with qualifying low error rate. In this factors were caused by the less ability of students in transforming the words to the question into a mathematical model that was appropriate, students were less thorough in Constructing a mathematical model, the lack of creative thinking abilities of students in pursuing a strategy is chosen, less of mastering the material, the students were unsual to write the final answer or conclusion, and in a hurry so did not check back to their work.